TICK SIZE DAN KUALITAS PASAR DI BURSA EFEK JAKARTA - Bahtiar Usman (Universitas Trisakti, 2007)
The purpose of this study is to analyze the impact of a tick size change announcement to capital market quality using data from firms listed in Bursa Effect Jakarta. Database classified firms by stock volume level and price level. Generally, there is no evidence to prove that a tick size change announcement have an influence to capital market quality, but for special case we can prove that a tick size change announcement tend to influence capital market quality: i.e for firm that have lower price stock, the reducing tick size announcement will decrease capital market quality and from regression result find that reducing tick size will also decrease capital market quality.Keywords: Announcements, tick size, capital market quality